2012
DOI: 10.1590/s1415-43662012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Incorporação de gesso para correção da salinidade e sodicidade de solos salino-sódicos

Abstract: Com o objetivo de avaliar o efeito da aplicação do gesso nas características químicas de solos salino-sódicos coletados no Perímetro Irrigado do Moxotó, localizado no município de Ibimirim, PE, um experimento foi realizado em colunas de solo instaladas no Laboratório de Mecânica do Solo e Aproveitamento de Resíduo da Universidade Federal Rural de Pernambuco. Os tratamentos foram dispostos em um delineamento inteiramente casualizado com esquema fatorial de dois solos (S1 e S2) e sete níveis da necessidade de ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
0
9
0
10
Order By: Relevance
“…The process of reclamation of the salinized soils consisted of the application of water at various depths for the leaching of fertilizer salts and reduction of the electrical conductivity. This was based on empirical considerations of the solute dynamics that recommends application of a water depth corresponding to twice the volume of pores, for fast calculation of the reclamation water depth for saline soils [11]. In a first step, an initial water depth was applied to raise the lysimeter soil to field capacity and only then were the reclamation washing depths applied.…”
Section: Calculation and Application Of The Washing Water Depths For mentioning
confidence: 99%
“…The process of reclamation of the salinized soils consisted of the application of water at various depths for the leaching of fertilizer salts and reduction of the electrical conductivity. This was based on empirical considerations of the solute dynamics that recommends application of a water depth corresponding to twice the volume of pores, for fast calculation of the reclamation water depth for saline soils [11]. In a first step, an initial water depth was applied to raise the lysimeter soil to field capacity and only then were the reclamation washing depths applied.…”
Section: Calculation and Application Of The Washing Water Depths For mentioning
confidence: 99%
“…Outra alternativa seria o uso de corretivos químicos como a aplicação do gesso (CaSO4.2H2O) para substituir o sódio pelo cálcio do complexo dos solos [35]. Este produto químico é de baixo custo e, segundo Tavares et al (2012) [36] apresenta bons resultados na redução dos níveis de salinização dos solos.…”
Section: Alternativas Para Correção E Aproveitamento Das áReas Impactunclassified
“…The incorporation of gypsum results in improvements in chemical properties, reflecting a decrease in salinity and sodicity of soils, and physical characteristics, such as increase in macroporosity and hydraulic conductivity of the soil. TAVARES FILHO et al (2012) also observed physical and chemical improvement when gypsum was used in the correction of saline-sodic soils in the irrigated area of Moxotó in the municipality of Ibimirim, PE.…”
Section: Chemical Attributes Of the Soil And Drainage Watermentioning
confidence: 88%